دور الزوج في مواجهة سرطان الثدي: كيفية التكيف مع التحديات العاطفية ودعم الزوجة بفعالية - Kmichou, Halima; Ziani, Aicha (Darul Yasin Al Sys, 2025)
The selection of this study was driven by a desire to analyze the psychological and social dimensions faced by couples in the context of breast cancer and how this illness affects their relationship. Additionally, the study aims to clarify the husband's role in supporting his wife throughout this challenging journey. The research seeks to understand the impact of the disease on marital relationships and how couples adapt to emotional and health-related changes. It relies on a systematic review of previous studies that explored the psychological and social effects of breast cancer, incorporating a selection of scientific research on couples facing the disease. The findings indicate that couples with effective communication and active participation in the treatment process are better equipped to adapt. Furthermore, shared medical decision-making, mutual emotional support, and joint coping strategies play a crucial role in reducing emotional distress. The study concludes that emotional support from the husband is a key factor in enhancing the wife's quality of life and enabling her to cope with her condition. This highlights the importance of developing counseling programs for spouses to help them navigate the challenges associated with the disease.